Development of Interactive Web-Based Augmented Reality for Human Digestive System in Class XI - Yanuar Rizky Prasetyo; Ence Surahman; Made Duananda Kartika Degeng (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2024)
This study aims to develop interactive, web-based augmented reality (AR) learning media for teaching the human digestive system to 11th-grade Biology students, addressing the practical limitations of application-based media. The goal is to enhance student engagement, material visualization, and learning outcomes without requiring additional app installations. The research followed the Sadiman development model, involving seven stages from needs analysis to product testing. Validation results for content and media indicated that the developed media is highly effective and suitable for use in the classroom. Trials were conducted with a small group of five students and a field test involving 30 students. The field test results showed a significant improvement in learning outcomes, with an average increase of 20.70%. Additionally, questionnaires revealed an approval rate of 83.41%, indicating that students found the media effective in understanding abstract concepts. In conclusion, the interactive, web-based AR learning media proved effective in improving students’ learning outcomes and interest in Biology. This media not only offers a valuable tool for enhancing education but also serves as a model for the development of future technology-based learning resources.